2018
DOI: 10.1007/s10843-017-0221-4
|View full text |Cite
|
Sign up to set email alerts
|

Coming out of conflict: How migrant entrepreneurs utilise human and social capital

Abstract: This paper examines how human and social capital influences the entrepreneurial activity of migrant entrepreneurs, with special reference to forced migrants due to conflict. The study uses Riinvest Migrant's Survey data collected at the end of 2008 and beginning of 2009 to estimate the probability of entrepreneurial activity among Kosovan migrants. The findings demonstrate that host networking (foreign spouse and foreign language fluency) exerts a positive effect on entrepreneurial activity of migrants, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 86 publications
1
41
3
Order By: Relevance
“…Furthermore, entrepreneurs that exit the business tend to be younger, more educated and lack entrepreneurial experience compared to entrepreneurs in the start-up or registration phase. Educational qualifications from the country of origin do not necessarily have influence on entrepreneurial process [83] if it is not supported by other complementary personal characteristic or business training in the host country.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, entrepreneurs that exit the business tend to be younger, more educated and lack entrepreneurial experience compared to entrepreneurs in the start-up or registration phase. Educational qualifications from the country of origin do not necessarily have influence on entrepreneurial process [83] if it is not supported by other complementary personal characteristic or business training in the host country.…”
Section: Resultsmentioning
confidence: 99%
“…Those entrepreneurs with a low education level and low language skills could not survive in the host county although they have previous entrepreneurial experience with agri-food industry, while those entrepreneurs who have a high/middle education level with middle language skills could survive with or without previous entrepreneurial experience [66], which indicates that previous experience in agriculture and/or entrepreneurship are compensatory. Being familiar with the host country language is important to build business relationships [83].…”
Section: Resultsmentioning
confidence: 99%
“…As for training and work experiences predictors, human capital and its investment (i.e., education and training experiences) have always occupied a central role in the literature (Bertson et al, 2006;Wittekind et al, 2010). Based on Becker's studies (1993), Williams and Krasniqi (2018) outlined human capital as the individuals' skills and knowledge fuelled by education and training. Early literature argued that workers with a higher educational level have higher occupational chances (Mincer, 1991).…”
Section: Antecedents Of Employabilitymentioning
confidence: 99%
“…For example, a study indicated that the value of remittances and investments from Swiss-based Kosovars, as well as their spending on family visits back home, probably exceeds the value of Swiss foreign aid for Kosovo [61]. Moreover, their contribution to the build-up of a local economic ecosystem in Kosovo through know-how transfer, investment and valuable business networks is likely to contribute more to the reduction of poverty and social inequality in the long run than all the publicly funded European aid programs in the region [62].…”
Section: Supporting Migrants In Their Endeavor To Upgrade Their Skills Out Of Self-interestmentioning
confidence: 99%